Analysis of Enabling Factors on Safety Awareness and Compliance of The Use of PPE in Plastic Sack Industry Workers Using The PLS-SEM Method - Clarissa Addikko Febryantie Yasmine; Dewi Kurniasih; Farizi Rachman (Jurnal Statistika Universitas Muhammadiyah Semarang, 2023)
A work accident is an unwanted and unanticipated event that can result in loss of life or property. The high incidence of work accidents can be caused by a lack of worker awareness of work safety. One of the elements in the PRECEDE-PROCEED behavior change theory, namely enabling factors, are factors that facilitate behavior or activities, such as providing facilities and infrastructure for workers to prevent work accidents. This study aims to ascertain the effect of enabling factors consisting of the availability of personal protective equipment (PPE) and training on safety awareness and adherence to the use of personal protective equipment (PPE) in plastic sack industry workers. This research is analytic using the PLS-SEM method. In this study, 81 participants were selected using a proportionate random sampling technique so that the number of samples used was comparable to the population in each sub-group using a questionnaire. Significant influences were observed in the results regarding the relationship between enabling factors and compliance with the utilization of personal protective equipment (PPE) (p-value = 0.000), as well as safety awareness (p-value = 0.000). Additionally, a significant influence was found between safety awareness and compliance with the use of personal protective equipment (PPE) (p-value = 0.019). Moreover, enabling factors were determined to influence compliance with PPE utilization through awareness (p-value = 0.035).